Dampak Khilafiah Dalam Bermazhab Terhadap Kohesi Sosial - Zamromi, M; Sumardi, Lalu; Fauzan, Ahmad (LP2M Universitas Islam Ahmad Dahlan, 2024)
This study examines the impact of Khilafiah in Bermazhab on Social Cohesion in Keroya Village, Aikmel District, East Lombok Regency. The purpose of this study is to determine the efforts made by the community in maintaining social cohesion. This research uses a qualitative approach with a type of case study research. Data collection techniques using interviews, observation, and documentation. The results of this study indicate that the impact of khilafiah in bermazhab on social cohesion in Keroya Village caused conflict due to the khotib in delivering sermons that blasphemed tahlilan. After that, there was a split that made two diversity groups, namely sunni and salafi. The existence of Salafism affected the social cohesion of the community. Previously, the community's social relations were very harmonious, this could be seen when carrying out religious activities such as tahlilan. At this point, the social cohesion of the community was disrupted because there was a Salafi religious group reluctant to attend religious activities. However, there is no conflict anymore because of the efforts made by the community in maintaining social cohesion which is influenced by several factors, namely, first, a fairly high level of education, second, strong religious values, and third, kinship ties.